Studi Kinerja Mesh Network untuk Penerapan Internet of Things (IoT) di Lingkungan Perkotaan - Fauzan Prasetyo Eka Putra; Maktsuful Ghummah; Moh. Amrullah; Rafli Hidayatullah (Pusat Riset dan Inovasi Nasional, 2025)
The Internet of Things (IoT) has become a crucial component in the development of smart cities, enabling seamless integration and communication among various devices to enhance public service efficiency. In densely populated and complex urban environments, a reliable and flexible communication infrastructure is essential. Mesh networks offer a promising solution due to their ability to provide dynamic connectivity, wide coverage, and resilience to node failures. This study aims to evaluate the performance of mesh networks in supporting IoT implementation in urban settings through a simulation-based approach. Key performance parameters analyzed include throughput, latency, packet delivery ratio (PDR), and energy consumption. Simulations are conducted by varying the number of nodes and network topologies to reflect real-world urban conditions. The results indicate that mesh networks can deliver stable and efficient communication performance in IoT scenarios, although challenges such as increased latency and reduced energy efficiency in large-scale deployments must be addressed. These findings offer valuable insights for the design and implementation of mesh-based IoT networks in urban environments.